PENGARUH EKSTRAK BIJI BENGKUANG TERHADAP WALANG SANGIT (Leptocorisa acuta Thunb.) PADA TANAMAN PADI - Evrialiani Rosba; Moralita Catri (Postgraduate, University of Mataram, 2015)
One of the biggest pests in rice plants were walang sangit (Leptocorisa acuta Thunb.) Where an attack by sucking plant fluids resulting grain hollow and fragile in the mill. In case of severe attack can reduce rice yields reached 100%. Attempts to control this pest is mostly done with synthetic pesticides. The use of synthetic pesticides can result in damage to the environment. To overcome such effects it is necessary to control that do not pollute the environment. One way to use botanical pesticides, namely yam seed extract. The purpose of this study was to determine the effect on the control of yam seed extract walang sangit (Leptocorisa acuta Thunb.) In rice plants. This study uses a completely randomized design (CRD) with 6 treatments and 3 replications. The treatments were A (0 g / L, B (10 g / L), C (15 g / L), D (20 g / L), E (25 g / L), F (30 g / L). Data mortality observations were analyzed by analysis of variance and continued with DNMRT test. Data were collected for the time of death walang sangit (L.acuta Thunb.) and mortality walang sangit (L.acuta Thunb). The results showed that the death walang sangit (L. acuta Thunb) The fastest is at a concentration of 30 g / L is 4.7 days and the slowest was 12.67 days, whereas the mortality walang sangit (L.acuta Thunb.) is the highest is at a concentration of 30 g / L is 63.3% and the lowest concentration of 0 g / L of 5%